Intraoperative Computed Tomography in Orthopaedic Trauma Surgery - Keil, Holger; Vetter, Sven Y.; Gruetzner, Paul Alfred; Franke, Jochen (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background When using mobile 3D C-arms, impairments in image quality occur due to artefacts caused by metal implants as well as to the limited field of view. To avoid these restrictions, special computed tomography devices were designed, in order to improve image quality and to meet requirements for intraoperative usage.
CRIS-Team WoS Importer:2021-05-21